Retromandibular Transparotid Approach for the Treatment of Benign Nontraumatic Conditions of the Mandible. A Retrospective Consecutive Case-Series Study. Issue 8 (November 2021) - Hauer, Lukas; Gencur, Jiri; Posta, Petr; Micopulos, Christos; Lišková, Veronika; Chalupová, Miroslava; Moztarzadeh, Omid
Abstract : Abstract: The retromandibular transparotid approach enables the most direct access to the central and posterior part of the mandibular ramus including the condylar region. So far it has not been widely used for the management of benign pathology of the mandible. The purpose of this study was to evaluate the utilization rate of this approach in the nontrauma setting including the determination of suitable indications for this access. In total, 105 patients with 107 retromandibular transparotid approaches performed in the 6.5 years (from May 2014 to November 2020) were evaluated. Patients suffering from nontrauma pathology accounted for 4.7% of all cases. The recurrences of different types of odontogenic cysts and secondary chronic osteomyelitis were surgically managed via this approach with aesthetically acceptable resultant scar achievement and no identified postoperative complications. All lesions resolved and no recurrences occurred during the follow-up 32.0 ± 20.7 months (range 6 to 59 months, median = 26 months). The retromandibular transparotid approach may be considered for the enucleation of benign bone lesions in selected patients. Another type of surgery for the management of benign nontraumatic conditions in an accessible area without requirements for continuity resection and jaw reconstruction may be also suitable for using this approach. Abstract : Supplemental Digital Content is available in the text